Diuretic Effect of Combination of Watercress (Nasturtium officinale) and Purslane (Portulaca oleraceae) - Sutjiatmo, Afifah Bambang; Yuliartati, Ni Luh Ade; Yulianti, Maulidya; Suryani, Suryani; Vikasari, Suci Nar (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Watercress (Nasturtium officinale) and purslane (Portulaca oleracea) are used to increase urination.This preclinical study aims to prove the diuretic effect of a combination of watercress and purslaneextracts. Simplisia of watercress and purslane herbs mixed with various combinations A (1:9), B(1:3) and C (1:1), then extracted in 50% ethanol. The animals were divided into five groups: control,furosemide 3.6 mg/kgBW, A 38 mg/kgBW, B 28 mg/kgBW, and C 10 mg/kgBW. Diuretic assay wascarried out using the modified Lipschitz method with the parameters observed were cumulative urinevolume for 6 and 24 hours, and potassium levels in 24-hour urine. The results showed the onset ofdiuretic effect of furosemide at 60 minutes, A at 150 minutes, B at 240 minutes and C at 90 minutes.Percent effectiveness of the diuretic in the furosemide was 718%, A 212%, B 231%, and C 368% whencompared to the controls. All combinations of extracts increased sodium and potassium secretion whencompared to controls, but this effect was not as strong as furosemide. All combinations of watercressand purslane herbs have a diuretic effect but weakly saluretic when compared to furosemide and thecombination that gives the best effect is combination C.